Lisensi Profesional Dalam Praktik Bimbingan Dan Konseling - Charisma Rahmadhani, Alifah; Budiman, Nandang; Nadhirah, Nadia Aulia (Universitas Palangka Raya, 2024)
uidance and counseling is an important profession in supporting the development of learners. Professional licensure is the practice of guidance and counseling has an important role to ensure the quality of services. The purpose of the study is to explain the importance of licensure in the guidance and counseling practice of counselors and counselees. The research method is Systematical Literature Review (SLR) which collects and evaluates research results. The results show that licensure is a sign of competence, qualification and permission letter of the counselor, to increase the trust of the counselee and protect from incompetent practices. In conclusion, professional licensure is an important element in improving the quality of guidance and counseling and needs to be further encouraged towards quality guidance and counseling practice.